Role of Tibetan Women in Carbon Balance in the Alpine Grasslands of the Tibetan Plateau. A Review. (1st January 2016) - Shang, Zhanhuan; White, Andrew; Degen, A. Allan; Long, Ruijun
Abstract : Males and females often contribute differently to the ecosystem as a result of their different roles and labour responsibilities. This is especially true in remote areas like the Tibetan alpine grasslands, where women handle most household chores and agricultural labour. Within this framework, women are involved physically in carbon balance to a much greater extent than are men. The collection and use of livestock dung for fuel (dung-fuel) and the production of livestock commodities are two female activities that are extremely important in the carbon cycle in grassland ecosystems. More than ninety per cent of fuel in the alpine grassland areas in China comes from livestock dung, which is collected and burnt by women. In addition, animal carbon leaves the grassland ecosystems through the selling of milk products by women. The burning of dung reduces the use of fossil fuels and wood in alpine areas, but causes severe indoor air pollution in homes and greatly increases health risks, mainly among women. Women should receive more education on and made aware of these dangers. Because of their heavy work load and busy time schedule, however, Tibetan women have little time for other activities. Consequently, their education is at an extremely poor level and their health issues are often neglected. Steps should be taken to improve the status of women in the community, involve them more in decision-making, promote their education and health standards, and encourage more gender equality in agricultural labour tasks. These changes for women have been implemented in other pastoral societies and have proven to be successful.